Bronchial and non‐bronchial systemic arteries: Value of multidetector CT angiography in diagnosis and angiographic embolisation feasibility analysis. Issue 6 (2nd April 2013) - Lin, Yuning; Chen, Ziqian; Yang, Xizhang; Zhong, Qun; Zhang, Hongwen; Yang, Li; Xu, Shangwen; Li, Hui
Abstract Introduction The aim of this study is to evaluate the diagnostic performance of multidetector CT angiography (CTA) in depicting bronchial and non‐bronchial systemic arteries in patients with haemoptysis and to assess whether this modality helps determine the feasibility of angiographic embolisation. Materials and Methods Fifty‐two patients with haemoptysis between January 2010 and July 2011 underwent both preoperative multidetector CTA and digital subtraction angiography (DSA) imaging. Diagnostic performance of CTA in depicting arteries causing haemoptysis was assessed on a per‐patient and a per‐artery basis. The feasibility of the endovascular treatment evaluated by CTA was analysed. Sensitivity, specificity, and positive and negative predictive values for those analyses were determined. Results Fifty patients were included in the artery‐presence‐number analysis. In the per‐patient analysis, neither CTA (P = 0.25) nor DSA (P = 1.00) showed statistical difference in the detection of arteries causing haemoptysis. The sensitivity, specificity, and positive and negative predictive values were 94%, 100%, 100%, and 40%, respectively, for the presence of pathologic arteries evaluated by CTA, and 98%, 100%, 100%, and 67%, respectively, for DSA. On the per‐artery basis, CTA correctly identified 97% (107/110). Fifty‐two patients were included in the feasibility analysis. The performance of CTA in predicting the feasibility of angiographic embolisation was not statistically different from the treatment performed (P = 1.00). The sensitivity, specificity, and positive and negative predictive values were 96%, 80%, 98% and 67%, respectively, for CTA. Conclusions Multidetector CTA is an accurate imaging method in depicting the presence and number of arteries causing haemoptysis. This modality is also useful for determining the feasibility of angiographic embolisation for haemoptysis.